Patient Service Care Information System (Case Study: Zainoel Abidin General Hospital Banda Aceh City) - Jannah, Rhauzatul; Fathurrahmad; Syarifuddin (Journal Dekstop Application (JDA), 2022)
Zainoel Abidin Aceh General Hospital is located in Banda Aceh City, Aceh Province, which is one of the health centers in the area. The growing community in the surrounding environment and even people from outside the region who continue to come for treatment at the Zainoel Abidin Aceh General Hospital require a good service to patients with the support of medical personnel and good staff who are expected to be able to provide professional health services this certainly cannot be separated from the management system in the hospital. The author limits the problem only to; How is the Patient Information System at the Zainoel Abidin General Hospital in Aceh and. Designing a Patient Information System at the Zainoel Abidin General Hospital Aceh using Visual BASIC.NET. From the description, the objectives of the discussion are; To find out the Patient Information System at the Zainoel Abidin Aceh General Hospital and Design a Patient Information System at the Zainoel Abidin Aceh General Hospital using Visual BASIC.NET. The Prototyping method is used as a software development model and evaluation activities are also carried out as an assessment of the results of the prototype being built. With this patient information system program, the information system at the Zainoel Abidin Aceh General Hospital becomes precise, and accurate, especially on the patient side. And to obtain information about the patient becomes easier; This information system is able to overcome the problems that often occur at the Zainoel Abidin Aceh General Hospital, namely the difficulty in controlling and supervising patients and planning for procurement of goods. This goods procurement information system can avoid excess patients and overcome the scarcity of goods which is certainly highly expected by business actors and The creation of an information system program in order to obtain quality information and Based on the evaluation of the current desktop application display With the prototype design, it is known that each category has an increase in the usability value. Content, Organization and Readability previously had a value of 0.62 and increased to 0.71. The Navigation category was previously 0.66 to 0.69. The previous User Interface Design category was 0.62 to 0.64 and the previous Performance and Effectiveness category was 0.67 to 0.78.